2015
DOI: 10.1007/jhep05(2015)108
|View full text |Cite
|
Sign up to set email alerts
|

A minimal supersymmetric E6 unified theory

Abstract: We show explicitly that supersymmetric E 6 Grand Unified Theory with a Higgs sector consisting of {27 + 27 + 351 ′ + 351 ′ + 78} fields provides a realistic scenario for symmetry breaking and fermion mass generation. While gauge symmetry breaking can be achieved without the 78 field, its presence is critical for a successful doublet-triplet mass splitting. The Yukawa sector of the model consists of only two symmetric matrices describing all of quark, lepton and neutrino masses and mixings. The fermion mass mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 112 publications
0
19
0
Order By: Relevance
“…This will allow us to have a large doublet-triplet splitting scale, which prevents rapid proton decay if the E 6 Yukawa relations were enforced. This will require either two pairs of (27,27) and one pair of (351 , 351 ) dimensional Higgs representations, or one pair of (27, 27), 78, and one pair of (351 , 351 ) dimensional Higgs representations (detailed studies of E 6 theories with broken Yukawa relations can be found in [49][50][51]). For our model, the unbroken symmetry at the TeV scale is…”
Section: The Model and Formalismmentioning
confidence: 99%
“…This will allow us to have a large doublet-triplet splitting scale, which prevents rapid proton decay if the E 6 Yukawa relations were enforced. This will require either two pairs of (27,27) and one pair of (351 , 351 ) dimensional Higgs representations, or one pair of (27, 27), 78, and one pair of (351 , 351 ) dimensional Higgs representations (detailed studies of E 6 theories with broken Yukawa relations can be found in [49][50][51]). For our model, the unbroken symmetry at the TeV scale is…”
Section: The Model and Formalismmentioning
confidence: 99%
“…Embedding SO (10) in larger gauge groups, for example E 6 cannot help [27,28] because the resulting theory is even less asymptotically free. One could envision different ways to go around this issue, for example one could push the unification scale closer to the gravity one via specific threshold corrections and hope that gravity will work its magic.…”
Section: Jhep12(2016)141mentioning
confidence: 99%
“…If a singlet scalar gauge invariant operator of the chiral ring 28) at the fixed point acquires 29) unitarity is violated unless it becomes free. If this occurs one needs to modify the a function accordingly [94] …”
Section: Gauge Invariant Fields Becoming Freementioning
confidence: 99%
See 1 more Smart Citation
“…This allows us to have a large doublet-triplet splitting scale, which prevents rapid proton decay if the E 6 Yukawa relations were enforced. This will need either two pairs of (27,27) or one pair of (27,27), 78, in addition to one pair of (351 ′ , 351 ′ ) dimensional Higgs representations (Detailed studies of E 6 theories with broken Yukawa relations can be found in [36,37].) For our model, the unbroken symmetry at the…”
Section: Introductionmentioning
confidence: 99%